2020
DOI: 10.1192/j.eurpsy.2020.87
|View full text |Cite
|
Sign up to set email alerts
|

Trends in (not) using scales in major depression: A categorization and clinical orientation

Abstract: Background. Standard depression rating scales like the Hamilton Depression Rating Scale and the Montgomery-Åsberg Depression Rating Scale were developed more than 40 years ago. They are mandatory in clinical trials but are for a variety of reasons seldom used in clinical practice. Moreover, most clinicians are less familiar with more recent trends or with some dilemmas in assessment tools for major depression. Methods. Narrative review. Results. Asssessment tools can be observer-rating or self-rating scales, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 65 publications
(81 reference statements)
0
8
0
Order By: Relevance
“…38 The disparity may lie in the fact that different races and depression rating scales are used in these studies, as different scales have distinct validity and reliability in evaluating depression. 39 Therefore, further studies are needed to reveal the specific mechanisms underlying the association between high plasma 5-HT levels and depression outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…38 The disparity may lie in the fact that different races and depression rating scales are used in these studies, as different scales have distinct validity and reliability in evaluating depression. 39 Therefore, further studies are needed to reveal the specific mechanisms underlying the association between high plasma 5-HT levels and depression outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…According to epidemiological data, the prevalence of depression is about 1.5-3 times higher in women than in men [ 21 , 22 ], and the gender distribution of the subjects in this study showed that women are about 3 times more likely to be depressed than men, which is consistent with the disease characteristics. In addition, in the traditional diagnosis of depression and anxiety, the depression self-rating scale, anxiety self-rating scale, and Hamilton anxiety scale are often selected, but these scales have more questions and complicated items, which are not conducive to use in natural population cohorts [ 23 ]; in contrast, the PHQ-9 and GAD-7 selected in this study have fewer questions, condensed items, and high reliability, which are more effective in cohort screening. After we found depression and anxiety judged on the basis of total scale scores were correlated with EGEG, the core items of the scale that reflect the core symptoms of depression and anxiety were also correlated with gastrointestinal electrical parameters (r > 0, p < 0.05), further suggesting that EGEG can objectively reflect anxiety-depression disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the clinical features of the differential diagnosis of UPD and BPD, the psychiatric symptoms used in the DSM-5-TR diagnostic guidelines are subjective and especially ambiguous in the early stages 10 , 29 . Correspondingly, scales for mental health ratings suffer from time-consuming, subjective answers, and inconsistencies among raters, which are not routinely used in clinicians’ daily practice 30 . On the other hand, world-wide epidemiological studies have found statistical differences in the course characteristics of UPB and BPD.…”
Section: Introductionmentioning
confidence: 99%